Longitudinal career construction counselling for a black female student experiencing career indecision - Maree, J.G. (South African Journal of Higher Education, 2025)
This article reports on the longitudinal effect of career construction counselling on a black female student experiencing career indecision. Purposive sampling was used to select an adolescent experiencing career indecision. An integrative, QUALITATIVE-quantitative methodology was employed as the research lens, and a longitudinal, seven-year, explanatory, single-participant study design was adopted. The Career Construction Interview (CCI), the Career Interest Profile (CIP), and the Maree Career Matrix (MCM) were used to elicit the participant’s many micro-life stories and key life themes and to co-construct her future career-life story narrative. Adapted thematic data analysis incorporating the analytic style proposed by Savickas was carried out to analyse the data reflexively. In the short term, the participant’s psychological self as a social actor was enhanced by confirming her career choice, and her psychological self as a motivated agent was promoted by bolstering her goal-setting capacity and sense of self. Longitudinally, her self- and career identity was clarified and her sense of hope rekindled (the self as an autobiographical author was strengthened). Future research should examine the short- and longer-term effects of the approach described here in diverse career counselling contexts. More information is needed on when drawing on the CCI as a standalone assessment intervention may suffice.